2019
DOI: 10.3390/en12163060
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Concept of Spent Mushrooms Compost Torrefaction—Studying the Process Kinetics and the Influence of Temperature and Duration on the Calorific Value of the Produced Biocoal

Abstract: Poland, being the 3rd largest and growing producer of mushrooms in the world, generates almost 25% of the total European production. The generation rate of waste mushroom spent compost (MSC) amounts to 5 kg per 1 kg of mushrooms produced. We proposed the MSC treatment via torrefaction for the production of solid fuel—biocoal. In this research, we examined the MSC torrefaction kinetics using thermogravimetric analyses (TGA) and we tested the influence of torrefaction temperature within the range from 200 to 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…It should be borne in mind that the calculated kinetic triplet is only the optimal mathematical fit of the equation to the experimental data and has no strict physical significance (reaction order) in this case. The activation energy calculated in this way is apparent: it only serves to correlate the model with the experimental data and has no meaning as in the definition [32]. It was also concluded that the methods of kinetic analysis using various heating rate results were more efficient than the method involving a single heating rate [2].…”
Section: Fract Mass Loss Activation Energy (Kj/mol) Lg (A/smentioning
confidence: 99%
“…It should be borne in mind that the calculated kinetic triplet is only the optimal mathematical fit of the equation to the experimental data and has no strict physical significance (reaction order) in this case. The activation energy calculated in this way is apparent: it only serves to correlate the model with the experimental data and has no meaning as in the definition [32]. It was also concluded that the methods of kinetic analysis using various heating rate results were more efficient than the method involving a single heating rate [2].…”
Section: Fract Mass Loss Activation Energy (Kj/mol) Lg (A/smentioning
confidence: 99%
“…Syguła et al [20] used mushroom spent compost as a feedstock material subject to torrefaction at a similar temperature and time range (200 to 300 • C, 20-60 min). The research was focused mainly on the evaluation of torrefaction kinetics, but it is another example of "waste-to-carbon" strategy, showing that wastes of different origin can be successfully turned into a valuable resource.…”
Section: Biochar Propertiesmentioning
confidence: 99%
“…In this work, the E a and the reaction rate constants were determined in isothermal conditions and a temperature range of 200-300 • C. The same conditions and temperatures were used previously by Pulka et al [56], who tested sewage sludge (SS) with high ash content, and Syguła et al [57] who tested spent mushroom compost (MSC). The E a for torrefaction process of elephant dung was 18 kJ•mol −1 , and k values were increasing with process temperature from 1.16 × 10 −5 •s −1 to 2.73 × 10 −5 •s −1 (from 200 to 300 • C), respectively.…”
Section: Thermogravimetric Analysis Of Raw Materials and Kinetic Parammentioning
confidence: 99%